The influence of heat rate and austenitization temperature on microstructure and hardness of Hadfield steel - Haris Wahyudi; Swandya Eka Pratiwi; Adolf Asih Supriyanto; Daisman Purnomo Bayyu Aji (Universitas Mercu Buana, 2023)
The As-Cast condition of Hadfield alloy usually contains (Fe, Mn)3C carbides around the austenitic grains, which promote brittleness, making the steel impractical in industry. Heat treatment is normally applied to reduce carbide content, lower carbides, and improve toughness. However, a complete austenitic structure is not attainable during solution treatment. The dissolution temperature and dissolution time are critical to obtaining complete carbide content. Furthermore, heating must be done slowly, and the quenching speed must be fast enough. This study examines the effect of heat rate and austenitization temperatures in the solution treatment on the microstructure and hardness of Hadfield steel. The heat rate of 3, 6 and 10 oC/min is selected to determine whether there is a change in the microstructure of Hadfield steel. The four austenitization temperatures of 1000, 1100, 1150 and 1200 oC are used to ascertain carbide dissolution into the austenite matrix. Grain boundary, hardness, and phase transformation will confirm the microstructural change and hardness properties. The optical microscope shows carbide content is reduced as the austenitization temperature increases. The consequence of carbide dissolution affects the hardness. Its hardness decreases as temperature increase due to the loss of carbide. The as-Cast specimen has the highest hardness of 227.8 HV30, and the lowest hardness is 176.7 HV30 belongs to a specimen that is heated up to 1200 °C and quenched into water. Grain size is measured by the line intercept method, which shows its increase as temperatures increase. The result of grain measurement is as follows: As-Cast 224.6 mm, T 1000 °C 323.3 mm, T1100 °C 409.2 mm, T1150 °C 1014.4 mm, T1200 °C 881.6 mm. SEM-EDS confirms that the main phase is austenite, and a small amount of carbide is detected in the austenite matrix.